Motivation and anxiety during the second COVID-19 lockdown in gym exercisers: The mediating role of affects and satisfaction with life - Antunes, R. (2022)
The present study aimed to analyze the association between motivation (self-determined and non-self-determined motivation), positive and negative affect, life satisfaction and state-anxiety in a sample of gym exercisers, during the 2nd COVID-19 lockdown in Portugal. Also, we aimed to analyze the possible mediating role of positive and negative affect and life satisfaction in the relationship between motivation and levels of state-anxiety. A total of 201 gym participants (30.42 ± 11.22) were enrolled in the present study, of which 116 (57.7%) were women and 85 (42.3%) were men. The survey included sociodemographic data as well as the subsequently validated instruments: the State-Trait Anxiety Inventory, the Positive and Negative Affect Schedule, and the Satisfaction with Life Scale. The results revealed a positive association between state-anxiety and negative affect (r = .69), controlled motivation (r = .33), and autonomous motivation (r = .25). Still, state-anxiety was negatively associated with positive affect (r = -.40) and with satisfaction with life (r = -.43),. In addition, the results of mediation analysis, revealed inconsistent mediation of positive affect and life satisfaction in the relationship between autonomous motivation and state-anxiety. However, a total mediation was observed through negative affect and life satisfaction in the relationship between controlled motivation and anxiety since the indirect effect (β = .27) is higher than the direct effect (β = .06). Overall, the results reinforce that positive affect and satisfaction with life could act as a possible buffer against state-anxiety in gym exercisers and, thus, should be considered in future interventions and studies.